Alteration of Fecal Microbiota Profiles in Juvenile Idiopathic Arthritis. Associations with HLA-B27 Allele and Disease Status - Di Paola, Monica; Cavalieri, Duccio; Albanese, Davide; Sordo, Maddalena; Pindo, Massimo; Donati, Claudio; Pagnini, Ilaria; Giani, Teresa; Simonini, Gabriele; Paladini, Alessia; Lionetti, Paolo; De Filippo, Carlotta; et al. (Frontiers in Microbiology, 2016)
Alteration of gut microbiota is involved in several chronic inflammatory and autoimmune diseases, including rheumatoid arthritis, and gut microbial "pro-arthritogenic" profiles have been hypothesized. Intestinal inflammation may be involved in spondyloarthropathies and in a subset of patients affected by Juvenile Idiopathic Arthritis (JIA), the most common chronic rheumatic disease of childhood. We compared the fecal microbiota composition of JIA patients with healthy subjects (HS), evaluating differences in microbial profiles between sub-categories of JIA, such as enthesitis-related arthritis (JIA-ERA), in which inflammation of entheses occurs, and polyarticular JIA, non-enthesitis related arthritis (JIA-nERA). Through taxon-level analysis, we discovered alteration of fecal microbiota components that could be involved in subclinical gut inflammation, and promotion of joint inflammation. We observed abundance in Ruminococcaceae in both JIA categories, reduction in Clostridiaceae and Peptostreptococcaceae in JIA-ERA, and increase in Veillonellaceae in JIA-nERA, respectively compared with HS. Among the more relevant genera, we found an increase in Clostridium cluster XIVb, involved in colitis and arthritis, in JIA-ERA patients compared with HS, and a trend of decrease in Faecalibacterium, known for anti-inflammatory properties, in JIA-nERA compared with JIA-ERA and HS. Differential abundant taxa identified JIA patients for the HLA-B27 allele, including Bilophila, Clostridium cluster XIVb, Oscillibacter and Parvimonas. Prediction analysis of metabolic functions showed that JIA-ERA metagenome was differentially enriched in bacterial functions related to cell motility and chemotaxis, suggesting selection of potential virulence traits. We also discovered differential microbial profiles and intra-group variability among active disease and remission, suggesting instability of microbial ecosystem in autoimmune diseases with respect to healthy status. Similarly to other chronic autoimmune and inflammatory diseases, different microbial profiles, as observed among different JIA subgroups compared to HS, and potential functional acquisition related to migration could promote inflammation and contribute to the disease pathogenesis.